Pengaruh Struktur Aktiva, Likuiditas Dan Pertumbuhan Penjualan Terhadap Struktur Modal Pada Perusahaan Subsektor Transportasi - Salsabila, Fadia (IJAcc, 2025)
This research aims to examine and analyze the influence of asset structure, liquidity and sales growth on the capital structure of transportation subsector companies listed on the Indonesia Stock Exchange for the period 2019 - 2023. Asset structure uses the Fixed Asset Ratio (FAR) measurement formula, liquidity uses the Current measurement formula Ratio and sales growth use the Sales Of Growth (SOG) measurement formula. The population used in this research was 36 transportation subsector companies listed on the Indonesia Stock Exchange. This research sample was obtained using a purposive sampling technique so that 10 companies were obtained with 50 financial report data. The research instrument used was SPSS version 30. The results of this research can conclude that asset structure has a significant effect on capital structure. Liquidity has no effect on capital structure. Sales growth has no effect on capital structure. As well as asset structure, liquidity and sales growth simultaneously influence the capital structure. Keywords: Asset structure, Liquidity, Sales Growth and Capital Structure